Blood-Based Biomarkers for Predictive Diagnosis of Cognitive Impairment in a Pakistani Population - Iqbal, Ghazala; Braidy, Nady; Ahmed, Touqeer (Frontiers in Aging Neuroscience, 2020)
Numerous studies have identified an association between age-related cognitive impairment (CI) and oxidative damage, accumulation of metals, amyloid levels, tau, and deranged lipid profile. There is a concerted effort to establish the reliability of these blood-based biomarkers for predictive diagnosis of CI and its progression. We assessed the serum levels of high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol, triglycerides, total cholesterol, selected metals (Cu, Al, Zn, Pb, Mn, Cad), and total-tau and amyloid beta-42 protein in mild (n = 71), moderate (n = 86) and severe (n = 25) cognitively impaired patients and compared them with age-matched healthy controls (n = 90) from Pakistan. We found that a decrease in HDL cholesterol (correlation coefficient r = 0.467) and amyloid beta-42 (r = 0.451) were associated with increased severity of CI. On the other hand, an increase in cholesterol ratio (r = −0.562), LDL cholesterol (r = −0.428), triglycerides, and total-tau (r = −0.443) were associated with increased severity of CI. Increases in cholesterol ratio showed the strongest association and correlated with increases in tau concentration (r = 0.368), and increased triglycerides were associated with decreased amyloid beta-42 (r = −0.345). Increased Cu levels showed the strongest association with tau increase and increased Zn and Pb levels showed the strongest association with reduced amyloid beta-42 levels. Receiver Operating Characteristic (ROC) showed the cutoff values of blood metals (Al, Pb, Cu, Cad, Zn, and Mn), total-tau, and amyloid beta-42 with sensitivity and specificity. Our data show for the first time that blood lipids, metals (particularly Cu, Zn, Pb, and Al), serum amyloid-beta-42/tau proteins modulate each other’s levels and can be collectively used as a predictive marker for CI.